A Study on Irregular Migration from Bangladesh to Malaysia through the Bay of Bengal and the Andaman Sea - Afzalur Rahman (Otoritas : Jurnal Ilmu Pemerintahan, 2020)
Irregular migration is an issue of great concern for today’s world. There are various factors which are responsible for this conundrum. These are overpopulation, natural disaster, poverty, illiteracy, lack of employment opportunities, for a better life etc. Thus, irregular migration has been a livelihood strategy for the millions of people worldwide for the long time. Bangladesh is one of the top countries of the world in terms of sending labor migrants. Every year thousands of Bangladeshis are migrating overseas either legally or by illegal means for a better livelihood.  However, in the last couple of years, total remittance flow was not satisfactory because of the diplomatic tension between Bangladesh and major migrants receiving countries. In addition, the new migrations policies of the Middle-Eastern countries which is the main destination points for Bangladeshi migrants in terms of single regions also have shrunk the scope. As a result, the number of irregular migrations from Bangladesh to Malaysia has increased. This paper attempts to unveil the key causes of irregular migration through the risky Bay of Bengal and the Andaman Sea by analysing the field data. It will focus on the case studies of the trafficking victims and their family members with focusing on why they took this dangerous path of irregular migration. It also argues for an effective mechanism to monitor the whole process of irregular migration from Bangladesh to Malaysia on an urgent basis.